Extremely high serum CA19-9 level along with elevated D-dimer in assisting detection of ruptured ovarian endometriosis. (31st December 2022) - Shuang, Ting; Wang, Yiran; Zhao, Lanbo; Zhang, Kailu; Yin, Panyue; Guo, Lin; Jing, Wei; Feng, Xue; Li, Qiling
Abstract: Background: To clarify clinical importance of serum CA19-9, CA-125, and plasma D-dimer (D-D) levels in detecting spontaneously ruptured ovarian endometriosis (OE). Materials and Methods: We retrospectively examined 173 patients with endometriosis out of 735 cases of OE between 2013 and 2019. Among these, 21 cases were diagnosed as "spontaneously ruptured" after surgery, while the remaining cases were unruptured. Venous blood was collected pre-operatively to detect CA19-9, CA-125, and D-D levels. A receiver operating characteristic curve analysis was applied to test clinical value of each marker. Results: Among the 21 patients with ruptured OE, 16 had a history of pelvic cysts, 19 claimed sudden onsets of lower abdominal pain, and fluid accumulation were detected in cul-de-sac in only six participants by ultrasound. For serological investigation, both CA19-9 and D-D were significantly elevated in the ruptured OE group (343.09 ± 367.67 U/ml vs. 36.84 ± 40.01 U/ml, 3.39 ± 4.90 mg/L vs. 0.43 ± 0.29 mg/L, both p  < .0001). The area under curve (AUC) value for the combination of CA19-9 and D-D was 0.975 (95% CI, 0.939 − 0.993), with specificity of 96.69%, and sensitivity of 85.71%. The combination of CA-125, CA19-9 and D-D showed the highest AUC value that up to 0.976 (95% CI, 0.940–0.993), with sensitivity of 95.24%, and specificity of 87.50%. Conclusion: The combination of CA19-9 and D-D can be chosen as an effective and economical indicators to identify patients with spontaneously ruptured OE in pre-operation assessment. However, from the perspective of differential diagnosis, the combination of CA-125, CA19-9 and D-D is the best choice. Key messages: Taking into account the economic effect, the combination of CA19-9 and D-D can be chosen as an effective indicators to identify patients with spontaneously ruptured OE in pre-operation assessment. From the perspective of differential diagnosis, the combination of CA-125, CA19-9 and D-D is the best choice to identify patients with spontaneously ruptured OE.